EFFORTS TO INCREASE THE ABILITY TO CHOOSE A SCHOOL GROUP COUNSELING SERVICES THROUGH ADVANCED CLASS IX SMP NEGERI 2 METRO STATE IN 2013 - Rohima, Rohima (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
SMP Negeri 2 Metro In reality, there are many confused students choose a major program of advanced studies, especially for junior high school students. It is necessary to learn / coaching to the students to be able to choose the school accordingly. Researchers conduct action research through the Guidance Counseling Group in Class IX student of SMP Negeri 2 Metro. The experiment was conducted using two cycles. Recapitulation of data Selecting a program majoring in the process of learning / coaching from the first cycle to the second cycle, there is an increase of 57.06% to 86.35%. The results of the data summary portfolio also increased from 33.32% to 83.33%, and the recapitulation of learning outcomes of students who otherwise Completed Pass also risen from 54.54% increase to 96.96%. Thus concluded indicator of success is to reach the target / as are 95% or more.Keywords: guidance group, select schools, smp negeri 2 metro